Cost per responder analysis of guselkumab versus targeted therapies in the treatment of moderate to severe plaque psoriasis in Germany. (17th February 2022) - Augustin, Matthias; Wirth, Daniel; Mahlich, Jörg; Pepper, Alicia N.; Druchok, Cheryl
Abstract: Background: The fully human monoclonal antibody guselkumab is an effective treatment option for patients with moderate to severe psoriasis. Objective: The objective of this study was to examine the cost per responder of guselkumab compared with other targeted therapies for the treatment of moderate to severe plaque psoriasis in Germany. Methods: A one-year cost per responder model was developed based on efficacy and safety data from a published network meta-analysis. Drug, treatment administration, resource use, and adverse event costs were included in the analysis. The primary analysis assessed the cost per Psoriasis Area and Severity Index (PASI) 90 responder at week 16. Additional analyses were conducted at year 1. In the year 1 analyses, treatment response was assessed at the end of the induction period (week 16) to determine which patients continued onto maintenance therapy (responders) and which patients moved onto a subsequent adalimumab or secukinumab therapy (non-responders). Results: At week 16, the cost per PASI 90 responder was lower for guselkumab than all comparators except adalimumab and brodalumab. Similarly, in the year 1 analyses, guselkumab had a lower cost per PASI 90 responder than all comparators except brodalumab. Conclusions: Guselkumab is a cost-effective therapy option in Germany.